Proceedings on Intelligent Systems and Knowledge Engineering (ISKE2007) 2007
DOI: 10.2991/iske.2007.238
|View full text |Cite
|
Sign up to set email alerts
|

A Course Recommender System Using Multiple Criteria Decision Making Method

Abstract: A recommender system is a specific type of information filtering technique that presents the userrelevant information, which is implemented by creating a user's profile and comparing it to the other existing reference characteristics stored in the database. This paper developed a course recommender system capable of helping prospective students to choose relevant post graduate courses by multiple criteria decision making method. First, the multiple criteria decision making method was given. Then, the system pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Hopefully, it seems, to a certain extent, feasible to discover what the user was about and/or what he intended to achieve while using techniques like in Mostow (2004). This can lead to the realization of a recommender system (Resnick and Varian, 1997; Le Roux et al , 2007).…”
Section: Evaluation Resultsmentioning
confidence: 99%
“…Hopefully, it seems, to a certain extent, feasible to discover what the user was about and/or what he intended to achieve while using techniques like in Mostow (2004). This can lead to the realization of a recommender system (Resnick and Varian, 1997; Le Roux et al , 2007).…”
Section: Evaluation Resultsmentioning
confidence: 99%
“…Examples are Grundy (Rich 1979) and (Le Roux et al . 2007). Context-based filtering : These RSs take into account external information, such as reviews and editorial data, together with user preferences and the item information.…”
Section: The Problemmentioning
confidence: 99%
“…Relevant literature has shown that usually career goals, personal interests, and background are factors that in uence students/applicants choice of programmes [1][2][3][4][5]. It has also been revealed by Ibrahim et al [1] that three out of every four students/applicants were tentative or uncertain about career goals, progression, and selection at the HEI entry.…”
Section: Introductionmentioning
confidence: 99%